1995
DOI: 10.1073/pnas.92.12.5734
|View full text |Cite
|
Sign up to set email alerts
|

Somatodendritic expression of an immediate early gene is regulated by synaptic activity.

Abstract: Trans-synaptic activation of gene expression is linked to long-term plastic adaptations in the nervous system. To examine the molecular program induced by synaptic activity, we have employed molecular cloning techniques to identify an immediate early gene that is rapidly induced in the brain. We here report the entire nucleotide sequence of the cDNA, which encodes an open reading frame of 396 amino acids. Within the hippocampus, constitutive expression was low. Basal levels of expression in the cortex were hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
542
1
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 644 publications
(563 citation statements)
references
References 44 publications
19
542
1
1
Order By: Relevance
“…Previous studies have established that the expression of Arc is activated by neuronal activity (1,2,4,5). Consistent with this finding, we found that the expression of Arc mRNA was also increased by the direct activation of NMDA receptor (NMDAR) with exogenously added NMDA (Fig.…”
Section: Proximal Region Of the Arc Promoter Wassupporting
confidence: 79%
See 1 more Smart Citation
“…Previous studies have established that the expression of Arc is activated by neuronal activity (1,2,4,5). Consistent with this finding, we found that the expression of Arc mRNA was also increased by the direct activation of NMDA receptor (NMDAR) with exogenously added NMDA (Fig.…”
Section: Proximal Region Of the Arc Promoter Wassupporting
confidence: 79%
“…The gene encoding activity-regulated cytoskeleton-associated protein (Arc), 3 also known as the activity-regulated gene of 3.1 kb (Arg3.1), is an immediate early gene (IEG), the expression of which is rapidly activated in response to neuronal activity (1,2). In neurons, Arc expression is regulated by various stimuli including not only neuronal activity, but also BDNF, cAMP, and PDGF (3)(4)(5)(6).…”
mentioning
confidence: 99%
“…Fos and Zif/268 are nuclear transcription factors that regulate the expression of late-target genes whereas the protein products of the effector genes, arc and bdnf, are rapidly expressed and delivered to activated synapses (Link et al 1995;Steward and Worley 2001;Ying et al 2002;Bozon et al 2003;Tongiorgi et al 2004). In addition, early phases of instrumental learning (Hernandez et al 2006;Kelly and Deadwyler 2003) elicit widespread zif/268 and arc induction throughout an extensive corticostriatal network in rats, whereas manipulation of BDNF levels in the brain alters cocaine-seeking in a regionally selective manner (Horger et al 1999;Lu et al 2004;Berglind et al 2007;Graham et al 2007).…”
Section: Functional Significance Of Gene Expression Changesmentioning
confidence: 99%
“…The hypothesis of dendritic translation has been strengthened in recent years by the discovery in dendrites of various types of mRNAs and nonmessenger RNAs. Dendritic mRNAs include, among others, those encoding: (1) the high molecular mass forms of microtubule-associated protein 2 (MAP2a / b; Garner et al, 1988;Bruckenstein et al, 1990;Kleiman et al, 1990), (2) the ␣-subunit of Ca 2ϩ /calmodulin-dependent protein kinase type II (CaMKII␣; Burgin et al, 1990); (3) the inositol 1,4,5-trisphosphate receptor type 1 (InsP 3 R1; Furuichi et al, 1993); (4) neurogranin (Ng / RC3; Landry et al, 1994); (5) a number of amino acid receptor subunits (Miyashiro et al, 1994;Racca et al, 1997); and (6) the cytoskeleton-associated protein Arc (Link et al, 1995;Lyford et al, 1995). Dendritic nonmessenger RNAs include BC1 RNA , ribosomal RNAs (rRNAs) (Kleiman et al, 1993;1994), and tRNAs .…”
Section: Abstract: Neuronal Bc1 Rna; Rna Transport; Dendrites; Targementioning
confidence: 99%